Sarawak Tua Pek Kong Heritage Trail - Elena, Chai; Wang, Yin Chai; Tan, Chong Eng; Lee, Nung Kion (Ministry of Tourism Creative Industry and Performing Arts & Universiti Malaysia Sarawak, 2024)
This book presents an important feature of Sarawak’s distinctive cultural heritage that could be brand as the state’s own tourism attractions. There are no other states in Malaysia that has as many Tua Pek Kong temples. There are 77 Tua Pek Kong temples all over Sarawak with one still in the middle of construction, the Long Lama Tua Pek Kong Temple. Thus, it is not an over exaggeration that Sarawak is home to the most Tua Pek Kong temples in Malaysia. This book features the history of the temples and its association with the community. As tangible assets, temples are venues that have witness to the changing physical and social environment. Many temples have been destroyed by fire, reconstructed, moved due to unavoidable circumstances. Community living by the temples coped with the changes and circumstances. The relationship between the temples and the community forms an intangible connection that are accompanied by emotions, memories and narratives that have been passed from generation to generation. Temples and the community portray the intrinsic relationship that bonds the place and people together.